Nursery and grow-out performance of hybrid grouper (Epinephelus fuscoguttatus × E. lanceolatus) cultured in concrete ponds - Arrosyid, Muchammad Aziz; Zidane, Muhammad; Maisaroh, Dian Sari (UIN Sunan Ampel Surabaya, 2025)
Hybrid grouper (Epinephelus fuscoguttatus × E. lanceolatus) is a high-value marine fish with significant economic potential in both domestic and export markets. Effective nursery and grow-out management is essential to optimize growth, survival, and overall productivity. This study aimed to evaluate the optimal application of nursery and grow-out techniques for hybrid grouper in concrete ponds at the Marine Aquaculture Installation (IBL) Boncong, Tuban, East Java, Indonesia. The research was conducted over 13 weeks (February–May 2025) using a descriptive approach through direct observation, interviews, active participation, and documentation. Nursery activities included pond preparation, fry selection, acclimatization, size grading, feeding management, and water quality monitoring, while the grow-out phase involved feed management and health maintenance in floating net cages. Results showed an average Specific Growth Rate (SGR) of 6.4% per day and a final survival rate (SR) of 86.25%, meeting the Indonesian National Standard (SNI) minimum requirement of 80%. Effective feeding and optimal water quality contributed to high growth performance and fish survival. These findings indicate that proper nursery and grow-out management is crucial for productive and profitable hybrid grouper aquaculture.